ANALYZING SERVICE QUALITY IN A HIGHER EDUCATION A Phenomenological Study - Rokhman, Wahibur (QUALITY, 2013)
The purpose of this paper is to explore, from students’ perspective, how students perceived the service quality in International IslamicUniversity Malaysia (IIUM). A phenomenological method wasused; it is a naturalistic approach to acquire information on students experience about the service quality that they are feelingthrough open-ended questioner, interviews and observations.The result reveals that students perceived the service quality indifferent ways. The study found that the university is performingfairly enough in term of physical facilities and academic staff, butin term of administration staffs less than students’ expectation. Thestudy recommends university’s management to give attention to thefollowing issues: to improve the quality of staffs, to improve the security guard in this campus and to reform or refine the office of CPS and Finance. Keywords: Quality, Service, Higher Education